Strategi Penguasaan Makna Leksikon Meishi Kategori Gutaitekina Mono oleh Tokoh Yotsuba - Ainie, Isnin; Ingrida, Rizka Nadia (Faculty of Letters, Dr. Soetomo University, 2021)
In General, meishi or noun is by far the most mastered lexicon for children especially those in the pre-operational stage (2-7 years old) where several strategies are used to increase the retention of vocabulary significantly. This study aims to identify the strategies used by Yotsuba, a 5-year-old protagonist of Yotsubato! in his journey to acquire the meaning of meishi, specifically, gutaitekina mono (concrete noun). This descriptive qualitative study used data from volume 1-10 of Yotsubato!. 30 data related to gutaitekina mono were extracted and further analysed using the framework by Gollinkof (in Dardjowidjojo, 2008:262-263). The finding shows that Yotsuba used 6 strategies to acquire the meaning of gutaitekina mono: novel nameless strategy (11 data) reference (10 data), extendibility (4 data), conventionality (2 data), object scope (2 data), and categorical scope (1 data). Novel name-nameless category is found to be the most used strategy while categorical scope was the least used. Keywords: gutaitekina mono; lexicon; meishi; strategies.